Formation of BN from BCNO and the development of ordered BN structure: I. Synthesis of BCNO with various chemistries and degrees of crystallinity and reaction mechanism on BN formation. Issue 13 (September 2018) - Örnek, Metin; Hwang, Chawon; Reddy, K. Madhav; Domnich, Vladislav; Miller, Steven L.; Akdoğan, E. Koray; Hemker, Kevin J.; Haber, Richard A.
Abstract: We synthesized BCNO compounds and investigated how the synthesis conditions impact i) BCNO formation, their chemistry and degree of crystallinity, and ii) BN formation from BCNO and its structural ordering. Heating boric acid (H3 BO3 ) and melamine (C3 H6 N6 ) mixture yields intermediate amorphous BCNO compound. Increasing the synthesis temperature, and H3 BO3 to C3 H6 N6 ratio promote BN formation and its structural ordering. We propose a possible reaction mechanism for BN formation from H3 BO3 and C3 H6 N6 mixture and we explain the observations based on thermodynamic and kinetic considerations. An increase in synthesis temperature promotes BN formation since the reactions are endothermic. An increase in H3 BO3 to C3 H6 N6 ratio promotes BN formation since theoretical BN formation temperature decreases with the above ratio. Furthermore, it enhances material transfer and mobility of the BN layer by forming B2 O3 phase. We also propose a processing-structure correlation map that can help determining experimental conditions for single-phase amorphous BCNO synthesis.